Pengaruh Diabetes Melitus Terhadap Mata - Sumiyati Sumiyati; Nisa Zakiati Umami; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Eyes are the window to life. Eyes are the most important and very meaningful sense that a person has. The eyes are the sense of sight that can be used to carry out daily activities. However, if someone's vision is disturbed, their activities will be disturbed. Many things can affect the quality of vision, one of which is diabetes mellitus. Diabetes mellitus can cause damage to the function of the eye and retina. Examples of diabetes mellitus in the eye are diabetic retinopathy, gaucoma and cataracts.